New Analytical Techniques for the Assay of Raltegravir (Anti-HIV Drug) - Annapurna, Mukthinuthalapati Mathrusri (Asian Journal of Pharmaceutics (AJP), 2018)
Introduction: Four first-order derivative, three difference and three zero-order spectrophotometric techniques were developed for the assay of Raltegravir in tablets. Materials and Methods: Spectrophotometric techniques such as zero order (D0), first-order derivative (D!) and difference spectroscopic methods have been developed in water and phosphate buffers (pH 3, pH 4, and pH 5) for the determination of Raltegravir. Results: Raltegravir has obeyed Beer-Lambert’s law 1–150 in zero order (D0) and 10–150 μg/mL in both first-order derivative (D!) and difference spectroscopic methods. Conclusion: Raltegravir has shown a wide range of linearity in all the methods, and all the methods were validated as per the ICH guidelines. These simple methods can be successfully applied for the assay of Raltegravir in tablets.